Experiencing problems of the health in family: the implementation of the theoretical-methodological proposal of care - Maria Angélica P Waidman; Aline F da Rocha; Ana Rita Z de Paschoa; Cremilde AT Radovanovic (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
The aim of this research was implement in part the theoretical-methodological proposal of care in the family of chronic diseases bearer, described by Waidman, and evaluate the obtained results. This assistance and convergent qualitative research was carried out between August of 2005 and June of 2006. Five families with a chronic disease bearer, assisted by the Public Health Service of Maringá city, in Paraná - Brazil, was studied. The approach strategies to the studied families were the home visits and the therapeutic groups. The analysis of the obtained data was carried out by contents analyses technique. The obtained results were presented in two categories, family characterization and experiencing the family health troubles. In spite of difficult, was observed that the family caregivers are willing to care of the ill, having affection with them. These facts are fundamental to keep family coexistence.